Implementasi Kode Etik Profesional Guru PAK dalam Membangun Integritas dan Keteladanan Kristen di Sekolah Menengah - Nurlela Syafrian Oematan; Henry Leonardi Sustanto; Jaminter Ompusunggu (REDOMINATE Jurnal Teologi dan Pendidikan Kristiani, 2026)
This study examines the application of the professional code of ethics for Christian Religious Education (CRE) teachers in building student integrity in secondary schools during the digital era. The primary issues discussed include the extent to which the code of ethics is implemented, its impact on students’ moral-spiritual standards, and the challenges of aligning professional ethics with a ministry calling. Using a library research approach, this study analyzes biblical texts, ethics textbooks, and scientific journals published within the last ten years. The findings indicate that the professionalism of CRE teachers must be grounded in Kingdom of God values by integrating pedagogical competence with theological calling through In-Persona Christi theory and the concept of vocatio. Authentic teacher exemplarity is identified as the most effective instrument for adolescent character formation amid the post-truth era, where digital information often blurs moral judgment. This study recommends a kenosis pedagogy approach, requiring educators to be authentically present, humble, and free from intellectual arrogance in order to achieve meaningful transformation of student character, integrity, and moral-spiritual maturity within contemporary Christian educational practice and school life contexts.